A vanishing legacy? threats and challenges in the conservation of the colonial era's Anglican ecclesiastical heritage in Yorubaland. Issue 2 (3rd May 2020) - Sabri, Reyhan; Olagoke, Oluseyi A.
ABSTRACT: The protection of colonial-era buildings as part of the modern heritage is now viewed more positively as part of the texture of urban memory and fabric. However, there are major challenges for the preservation of ecclesiastical buildings erected in Christianized non-Western territories during the European colonial era. By utilizing physical observations, interviews and primary documents, this paper examines the current conservation state of colonial-era Anglican ecclesiastical heritage as well as the mechanics of their upkeep, using the early church buildings in Yorubaland (South West Nigeria) as the empirical focus. This article raises questions about challenges and threats to their protection, revealing the deficiencies in conservation know-how and problems with the current management structure, in particular the way the original buildings' fabric is modified or the building demolished to create more space. The paper proposes a set of recommendations for building institutional capacity for a better way forward. The example of Anglican ecclesiastical heritage in Yorubaland offers insights into colonial-era's heritage in sub-Saharan Africa and elsewhere.